If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1/2x+3(0)=-3
We simplify the equation to the form, which is simple to understand
-1/2x+3(0)=-3
Reorder the terms in parentheses
/2x+()=-3
Remove unnecessary parentheses
+/2x0=-3
We move all terms containing x to the left and all other terms to the right.
+2x=-3-0
We simplify left and right side of the equation.
+2x=-3
We divide both sides of the equation by 2 to get x.
x=-1.5
| 2log(2x)=1 | | -6=3-m | | 125n^2-45=0 | | 0.04x+0.03(x-20)=1.25 | | 6x-61=-3x+65 | | 4(w+1)+4=20 | | 5x-3=6x-7 | | -3e+2=5e-4 | | 3-.75x=8 | | 8b^2+10b+3=0 | | 7x-10=-2-x | | f(25)+f(26)= | | -150+9x=122-8x | | 3(r-8)-(-4)=7 | | 6-4x=5x-12 | | 2(c+3)=-9 | | 4r^3+11r^2-3r=0 | | 2(m-7)=4 | | -47-11x=-3x+73 | | 8x+3+2x+17=180 | | 14x-32=24 | | 5-.666x=1 | | 0.2x+0.3=-0.5 | | -6-20=2n+4(1-3n) | | y=7.50x+25 | | 6-.25x=9 | | 2x^2+4x^3+x^4=0 | | -47-11x=-33x+73 | | 3-2*(x+2)=3 | | 19x+10=87 | | 4a-2=26 | | x-76=-4x+64 |